2008
DOI: 10.1007/s00464-008-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal oxidative stress following CO2 pneumoperitoneum-like conditions

Abstract: Background Physiologic renal changes associated with pneumoperitoneum (PNP) have been described and various underlying mechanisms have been suggested. We investigated the possibility that PNP-associated renal damage is pressure dependent, and that oxidative stress is thereby involved. Materials and methods Seventy Wistar rat kidneys (n = 10 per group) were isolated. They were perfused with oxygenated, warm, Krebs-Henseleit solution containing 5% albumin within an isolated environment and subjected to various C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(47 reference statements)
4
14
0
1
Order By: Relevance
“…In line with our in vivo protocols, use of a unique ex vivo perfused kidney in a closed chamber [40] demonstrated that increasing CO 2 pressures from 0 mmHg (control), to 3,5,8,12,15, and 18 mmHg for 60 min decreased renal flow and urine output proportionately to the applied pressure. These changes were associated with reduced oxygen extraction in all the pressurized groups.…”
Section: Discussionsupporting
confidence: 66%
“…In line with our in vivo protocols, use of a unique ex vivo perfused kidney in a closed chamber [40] demonstrated that increasing CO 2 pressures from 0 mmHg (control), to 3,5,8,12,15, and 18 mmHg for 60 min decreased renal flow and urine output proportionately to the applied pressure. These changes were associated with reduced oxygen extraction in all the pressurized groups.…”
Section: Discussionsupporting
confidence: 66%
“…Pneumoperitoneum was induced by 10 mmHg CO 2 insufflation by 1 and 3 h [11,12]. After deinsufflation and recovery from the anesthesia, the animals were returned to their original cages and given free access to water and standard rat chow (Nuvilab, Colombo, Brazil).…”
Section: Induction Of Pneumoperitoneummentioning
confidence: 99%
“…The effects of intraabdominal pressure during pneumoperitoneum have been reported in rat and pig animal models [9,13,14,15,16]. These reports were based on normal kidneys.…”
Section: Discussionmentioning
confidence: 99%